Analisis Pengaruh Strategi Marketing Media Sosial Terhadap Minat Beli Pengunjung UMKM Coffeeshop di Kota Pangkalpinang - ., Yusnia; ., Sarwindah (CV. ITTC INDONESIA, 2025)
Social media today is not only limited to users' blogs but also as one of the values of a consumer's trust in buying any product offered, especially coffee shops. This study was conducted to test and analyze the influence of social media marketing strategy (X) on the buying interest of visitors (Y) of coffee shop MSMEs in Pangkalpinang City. In this study, the respondent population was taken in the vulnerable age range of 15-29 years, the age most active in using social media. This study is a quantitative research that focuses on correlation and linear regression tests. The results of this study show that the influence of social media marketing strategies has a positive effect on buying interest. Therefore, MSMEs must continue developing and implementing marketing strategies on social media to attract more customers.